Financial Distress Dengan Model Altman Dan Springate - Firda Nosita; Jumriaty Jusman (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Islamic Banking in Indonesia is faced with increasingly fierce competition with conventional banking. The low market share, the low literacy and the limited asset or human resources are the problems of islamic banking in Indonesia. Islamic Banking needs to asses the health of its business in order to measure how strong they can survive amid the e-business and fintech era nowadays. The study measure the financial health of the national foreign exchange Islamic banks consisting of four banks using the Altman Z-Score and Springate S-Score methods. The data obtained from financial report and use the ratios to calculate the score. By using Altman Z-Score, four of bank namely BNI Syariah, Bank Mega Syariah, Bank Muamalat and Bank Syariah Mandiri are in the “safe” zone. While, by using Springate S-Score, Bank Muamalat tend to be has financial distress with an S-Score value below of 0,862. The financial distress is strongly influenced by the amount of sales, profits, asset management and the level of Non Performing Financing (NPF). Islamic banking need to develop the product and service innovation and also improvement in financing management. In addition, islamic banking is also required to expand its market share by utilizing information and technology to be able to compete with conventional banking.